Cultura informacional e distinção: a orkutização sob o olhar social da Ciência da Informação - Ruleandson do Carmo Cruz (2014)
It studies information social networks about orkutization formed by information subjects who are users of the sites Facebook, Twitter and Orkut, with focus on their information practices and information culture, as well as on the social class representation created by them. Presents as object of study: the set of information subjects that debates on orkutization on the sites Facebook, Orkut e Twitter; the set of sites and/or blogs that talks about orkutization recovered by Google; and the set of photographs about orkutization posted on the application Instagram published at the page Pobregr.am. Considers as its empirical universe: 32 posts from 32 Facebook users profiles; 585 post from 295 Twitter users profiles; 292 posts from 278 Orkut users profiles; 100 sites and/or blogs with content about orkutization recovered by Google; 907 photos posted on the blog Pobreg.ram. Methodologically, structures itself as a multiple incorporated cases study. Cross-validates the methodology of information practices and culture. Also cross-validates data collected from the documentary analysis of blogs, foruns and profiles maintained by information subjects, as well as interviews with 15 of such subjects. Elaborates the theoretical approach under some of the main theories and theorists of seven thematic axis: social class; distinction; social networks; information practices; information subjects; information culture and social representations. Identifies the main social representations of orkutizaton presented by these subjects such as: orkutization as a bad use of sites; orkutization as popularization; orkutization as the presence of poor web users at the sites. Classifies the most frequent social class representation shown by the subjects such as: privilege class - the non-orkutized class, people who are supposed to know how to use the sites that post informations about a sophisticated life style; and popular class - the "orkutized class", the ones who cant use the mentioned sites properly and wich post informations about a humble life style. Outlines the studied information subjects general profile: adults, men and middle class members. Draws the information culture and distinction cicle on virtual social networks, composed by for four stages and during wich the information practices and cultures became ways of social distinction and, for such reason, then new information practices and culture are adopted by the subjects, and so on. Concludes, among other findings, that the researchs central thesis is true: the information culture can be a social distinction factor among users of sites concerned to virtual social network formation.